Architectural semiotics: a critical assessment of the work of Diana Agrest and Mario Gandelsonas - Bremner, Lindsay Jill (My University, 2016)
Since the late 1950's, research into architecture by many theoreticians has focused on its capacity to convey meaning. As well as traditional approaches to this question, mathematics, communication theory, semiotics, discourse analysis and deconstructive criticism have been used. The work of Diana Agrest and Mario Gandelsonas in the 1970's drew on a number of sources from the broader semiotic field to analyse architecture as a system of meaning. They focused on the processes involved in this aspect of architectural production. This dissertation examines their thesis, in order to ascertain whether the semiotic approach adequately explains how meaning is conveyed in architecture.
A thesis submitted to the Faculty of Architecture, University of the Witwatersrand, in fulfilment of the requirements for the Degree of Master of Architecture. Johannesburg 1991